Surgical outcome comparison between endoscopic septoplasty and conventional septoplasty among patients with nasal septal deviation - Sharath Babu, K.; Shankar, R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: When compared with standard head light technique, endoscopic septoplasty provides important advantages which include adequate visualization, room for instrumentation during functional endoscopic sinus surgery, access to para nasal sinuses and for other surgeries like trans-septal approach to the sphenoid sinus, visualization and stoppage of post-nasal bleeds. The aim of the study was to assess and compare the surgical outcome between endoscopic septoplasty and conventional septoplasty techniques in terms of anatomical correction and its complications. Methods: A prospective clinical study was conducted on hundred patients with nasal obstruction. Group A patients (n=50) underwent conventional septoplasty and group B (n=50) patients were operated by endoscopic septoplasty technique. Patients were subjected to diagnostic nasal endoscopy examination before and after surgery. Post-operative complications like trauma to lateral wall of nose, injury to cribriform plate, post-operative epistaxis, post-operative septal hematoma and septal abscess if occurred were noted. Results: Post-operatively diagnostic nasal endoscopy results show that there was a statistically significant improvement in endoscopic septoplasty group compared to conventional septoplasty and similarly the mean nasal obstruction symptom evaluation score. The most common post-operative complications which were occurred are synechiae and septal perforation and both these complications were more common among the conventional septoplasty group and the difference was found to be statistically significant. Conclusions: The study showed a better surgical outcome with a lesser complication among the endoscopic septoplasty as compared to conventional septoplasty. The only disadvantage of using endoscopic septoplasty was of binocular vision and repeated cleaning of the endoscope.